Sensitivity and Spesificity of Interleukin 18 as Biomarker for Acute Kidney Injury - Febri Jaya Gunawan; F Heru Irwanto; Andi Miarta; Theodorus Theodorus (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2018)
Background : Incidence of AKI in intensive care unit patients reach 60-70%, and the mortality rate is about 60%. IL-18 is a pro-inflammatory cytokine which increased in endogenous inflammation process. Studies in human showed that IL-18 concentration increased prior to AKI. Objective : The aims of this research is to determine the sensitivity and specificity of Interleukin-18 urine examination as an early biomarker for acute kidney injury. Methods : There’re total of 66 subjects who met the inclusion criteria. All the subject were checked for the IL-18 urine level with Cloud Clone kit and creatinine serum were also checked 48 hours after admission. Results :The results showed in the cut-off point of 411.25 Pg/mL , urine IL-18 has a sensitivity of 54.3 % and specificity 83.9%, positive predictive value 79.17%, negative predictive value 61.9% and accuracy of 68.18% Conclusions : Our result suggest that IL-18 urine holds a promise as an early biomarker of AKI and more sensitive and specific as an early biomarker for AKI compared to creatinine serum. Key words : Acute Kidney Injury, Interleukin-18, sensitivity, spesificity